POLA PRODUKSI BAWANG MERAH DI DESA SUMLILI KECAMATAN KUPANG BARAT: PENDEKATAN ANALISIS HIERARKI PROSES - Endeyani Vivitrida Mohamad; Maria Susana Medho (Politeknik Pertanian Negeri Kupang, 2021)
This research was conducted in May - June 2020. The aim research are; knowing pattern shallot production. The results showed; the monoculture production pattern of shallots was in two growing seasons (MT). MT I in March-May and MT II in June-August. The average production is 12.5 tonnes/ha, the potential shrinkage is 10% small and damaged tubers. Intensive cultivation technology uses tractors, suction water for irrigation, routine anorganic fertilization, chemical and mechanical disease control. Production costs Rp.506,500, cost goods sold Rp. 2,850/kg. The average selling price MT I Rp. 20,000/kg and MT II 10,000/kg. Number unsold products and damaged without treatment 20%. The results of analytical hierarchy process showed the decision to apply processing technology to increase added value needs to consider the marketing and selling price product, then determine number production and processing fried onions is highest priority. Key Words: Pattern of shallot production, analytical hierarchy process (AHP)